Probing Interstellar Grain Growth through Polarimetry in the Taurus Cloud Complex - Vaillancourt J. E.; Andersson B. -G.; Clemens Dan P.; Piirola Vilppu; Hoang Thiem; Becklin Eric E.; Caputo Miranda (Institute of Physics Publishing, Inc., 2022)
The optical and near-infrared (OIR) polarization of starlight is typically understood to arise from the dichroic
extinction of that light by dust grains whose axes are aligned with respect to a local magnetic field. The size
distribution of the aligned grain population can be constrained by measurements of the wavelength dependence of the polarization. The leading physical model for producing the alignment is that of radiative alignment torques (RAT), which predicts that the most efficiently aligned grains are those with sizes larger than the wavelengths of light composing the local radiation field. Therefore, for a given grain size distribution, the wavelength at which the polarization reaches a maximum (max) should correlate with the characteristic reddening along the line of sight between the dust grains and the illumination source. A correlation between max and reddening has been previously established for extinctions up to AV 4 mag. We extend the study of this relationship to a larger sample of stars in the Taurus cloud complex, including extinctions AV > 10 mag. We confirm the earlier results for AV < 4 mag, but find that the max vs. AV relationship bifurcates above AV 4 mag, with part of the sample continuing the previously observed relationship. The remaining sample exhibits a steeper rise in lambda_max vs. AV . We propose that the data exhibiting the steep rise represent lines of sight of high-density “clumps”, where grain coagulation has taken place. We present RAT-based modeling supporting these hypotheses. These results indicate that multi-band OIR polarimetry is a powerful tool for tracing grain growth in molecular clouds, independent of uncertainties in the dust temperature and emissivity.